2021
DOI: 10.1186/s11556-021-00257-x
|View full text |Cite
|
Sign up to set email alerts
|

Peer-led exercise program for ageing adults to improve physical functions - a randomized trial

Abstract: Background A peer-led exercise program is one way to empower people sharing similar characteristics to encourage others to be active, but there is a lack of evidence that these programs have physical function and other benefits when delivered to ageing adults. Methods This randomized controlled trial lasting 12 weeks proposed an exercise peer-led program offered to 31 adults aged 50 and above, twice a week, by a trained leader of the same age from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It is recommended that future studies include adherence rates, as well as withdrawal/retention rates, to better understand the value of utilizing peers in physical activity interventions. Two studies by Dorgo and colleagues [ 19 , 27 ] reported a 75% adherence rate, and Bouchard et al found that 68% of the intervention sessions were attended by their participants [ 21 ]. RT programs without peer support have reported withdrawal rates of up to 44% for older adults [ 46 , 47 , 48 ], indicating growing evidence of the benefits of including peers in physical activity interventions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is recommended that future studies include adherence rates, as well as withdrawal/retention rates, to better understand the value of utilizing peers in physical activity interventions. Two studies by Dorgo and colleagues [ 19 , 27 ] reported a 75% adherence rate, and Bouchard et al found that 68% of the intervention sessions were attended by their participants [ 21 ]. RT programs without peer support have reported withdrawal rates of up to 44% for older adults [ 46 , 47 , 48 ], indicating growing evidence of the benefits of including peers in physical activity interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the effects of using peer support [ 13 , 14 , 15 , 16 ], peer mentors [ 17 , 18 , 19 , 20 ], or peer leaders to deliver physical activity interventions [ 21 , 22 , 23 , 24 , 25 , 26 ]. Many included a mix of endurance, flexibility, strength, and balance training within the intervention [ 13 , 14 , 17 , 18 , 19 , 21 , 22 , 23 , 26 , 27 , 28 ], with an additional study exploring aquatic exercise [ 29 ]; two studies used walking only interventions [ 15 , 16 ], and one utilized only strength and balance training and was peer-led [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most utilised type of PPI for older adults was reminiscence interventions, which use past experiences to support psychological wellbeing. Similarly, peer-led programs, which mostly focus on physical activity, general wellbeing, and/or nutrition, have been shown to improve a vast range of health and wellbeing measures in older adults in the community [82], as well as those in retirement living [83].…”
Section: Peer-led Ppis For Older Adults and Aged Care Settingsmentioning
confidence: 99%